Exercise improves mental health status of young adults via attenuating inflammation factors but modalities matter - Liu, Jianxiu; Zhang, Yao; Li, Xingtian; Wang, Dizhi; Shi, Bolan; You, Yanwei; Min, Leizi; Luo, Bicheng; Li, Yanchun; Di, Qian; Ma, Xindong (Frontiers in Psychiatry, 2022)
Abstract Purpose: It is still unclear which exercise mode is optimal for protecting mental health and its association with the immune system. This study aimed to compare the intervention effect of high-intensity interval training (HIIT) and moderate-to-vigorous intensity continuous training (MVCT) on mental health and assess the underlying mechanism of exercise interventions to improve the immune system, which facilitated the mental health status. Methods: This is a double-blinded RCT study conducted from October 13, 2020 to January 25, 2021 (ClinicalTrials.gov identifier: NCT04830059). Ninety-three participants who met the inclusion criteria were randomized into the HIIT (N=33), MVCT (N=32), and control groups (N=28) with a mean age of 25.26 (SD = 2.21), and 43% of males enrolled in the study. Professional coaches guided participants in HIIT and MVCT groups to perform 40 minutes of exercise training three times a week for 12-week while those in the control group received one hour of health education twice a week. Questionnaires related to mental health status and blood samples of inflammatory factors, including immunoglobulin A(IgA), immunoglobulin M (IgM), albumin (Alb), globulin (GLO), lymphocytes (LYM), and lymphocyte percentage (LYM) were assessed before and after the intervention. Results: We found that blood inflammation factors increased significantly in the control group after 12 weeks, and both MVCT and HIIT intervention could effectively defend the increased inflammatory response compared with the control group. However, the MVCT intervention modality was more conducive to enhancing positive affect ( = 0.52, p = 0.018) and well-being ( = 1.08, p = 0.035) than HIIT. Furthermore, decreased IgA, Alb, and Glo were associated with improved mental health. Conclusion: Both 12-week HIIT and MVCT are beneficial to the immune system. The MVCT intervention mode is recommended to prevent mental health problems and attenuate immune inflammation, and the immune system is a potential mechanism that exercises improving mental health.